2018
DOI: 10.6065/apem.2018.23.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up to near final height of auxological changes in girls with idiopathic central precocious puberty treated with gonadotropin-releasing hormone analog and grouped by pretreatment body mass index level

Abstract: Purpose Reported changes in body mass index (BMI) in central precocious puberty (CPP) during and after gonadotropin-releasing hormone analog (GnRHa) treatment are inconsistent. We, therefore, investigated auxological parameters in GnRHa-treated girls with idiopathic CPP (ICPP) until attainment of near final height (NFH). Methods From the medical records of 59 ICPP girls who attained NFH after GnRHa therapy, auxological changes were compared between overweight (BMI≥85th percentile) and normal-weight (BMI<85th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
4
7
0
2
Order By: Relevance
“…A number of researchers have investigated FAHs after long-term treatment of children diagnosed with CPP. The majority of these authors reported that height gain, which is the difference between the FAH and the initial predicted adult height, was between 2.0 cm and 9.8 cm, similar to the results obtained in our study [ 6 , 7 , 15 21 ]. Most authors analyzed the adult height compared with PAH based on patients’ bone age before treatment.…”
Section: Discussionsupporting
confidence: 91%
“…A number of researchers have investigated FAHs after long-term treatment of children diagnosed with CPP. The majority of these authors reported that height gain, which is the difference between the FAH and the initial predicted adult height, was between 2.0 cm and 9.8 cm, similar to the results obtained in our study [ 6 , 7 , 15 21 ]. Most authors analyzed the adult height compared with PAH based on patients’ bone age before treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In the setting of CPP and early puberty, some [ 79 , 80 ] but not all [ 81-84 ] studies have reported that obese girls display more exaggerated BA advancement compared with nonobese girls. In one study by Park et al, in which BA was similarly advanced (2 years) in obese and nonobese girls, predicted adult height (PAH) was significantly lower than MPH in the nonobese group, while PAH and MPH were not significantly different in the obese group.…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…Both groups also showed significant improvement in PAH and height SDS for BA while on therapy, attaining near adult heights comparable to their MPH [ 89 ]. As noted above, Park et al also found that obese children improved their PAH while on GnRHa therapy and reached near final heights exceeding their MPH [ 81 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations